Effectiveness of antioxidants on the stability of banana chips - Noor, Napisah; Augustin, M. A. (Society of Chemical Industry, 1984)
The effectiveness of butylated hydroxyanisole (BHA) and butylated hydroxytoluene (BHT) in improving the stability of banana chips stored at 65°C were compared. Criteria used in the assessment of the stability of the chips included the determinations of peroxide, p-anisidine, acid and iodine values, E1cm1% at 232 amd 268 nm and the C18:2/C16:0 ratio of oil extracted from banana chips. It was found that chips fried in refined, bleached and deodorised (RBD) olein containing BHA or BHT were more stable than chips fried in RBD olein without antioxidants. BHT was more effective than BHA in prolonging the shelf-life of of banana chips. The same order of effectiveness of the antioxidants was observed at 65°C and at room temperature (25°C).